Reoccurrence of Stroke in a Patient With Peri-Device Leak of WATCHMAN Device. (July 2020) - Perkins, Jordan; Bhagat, Riwaj; Nichols, Matthew; Shah, Jignesh
Atrial fibrillation is the leading cause of cardioembolic stroke, with emboli most commonly originating from the left atrial appendage. We report the case of a 71-year-old male with left atrial appendage closure via implantation of the WATCHMAN device, due to possible anticoagulation therapy failure and increased bleeding risk, following a stroke. Following a new stroke over a year later, a 1.8-mm peri-device leak was observed. Surgical records noted a minimal (<5 mm jet flow) peri-device leak after the installation, which was considered successful WATCHMAN implantation per protocol. This case highlights the persistent risk of cardioembolic stroke in patients with nonvalvular atrial fibrillation despite device implantation and questions the significance of peri-device leak and further management with anticoagulation for recurrent stroke.